Integrated Resource Strategic Planning and Power Demand-Side Management - Hu, Zhaoguang; Han, Xinyang; Wen, Quan.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Integrated Resource Strategic Planning and Power Demand-Side Management elaborates two important methods - Integrated Resource Strategic Planning (IRSP) and Demand Side Management (DSM) - in terms of methodology modeling, case studies and lessons learned. This book introduces a prospective and realistic theory of the IRSP method and includes typical best practices of DSM for energy conservation and emission reduction in different countries. It can help energy providers and governmental decision-makers formulate policies and make plans for energy conservation and emission reduction, and can help power consumers reduce costs and participate in DSM projects. Zhaoguang Hu is the vice president and chief energy specialist at the State Grid Energy Research Institute, and the head of the Power Supply and Demand Research Laboratory in China.
Basic Theory of Integrated Resource Strategic Planning (IRSP) -- Basic Theory of Demand-side Management (DSM) -- The Director of Demand-side Management (DSM) -- Government -- The Implementers of Demand-side Management (DSM) ---Power Grid Enterprises -- The Backbone of DSM Implementation $1 (BEnergy Service Companies (ESCOs) -- The Important Participants in Demand-side Management (DSM) ---Power Consumers -- The Prospects of Demand-side Management (DSM) -- Introduction to a Demand-side Management (DSM) Laboratory.s
Keywords: Production of electric energy or power; Engineering economy; Energy; Energy Policy, Economics and Management; Energy Economics; Power Electronics, Electrical Machines and Networks